2015
DOI: 10.1002/alr.21474
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 as a novel regulator of basic fibroblast growth factor in chronic rhinosinusitis with nasal polyposis

Abstract: Background The immunopathogenesis of chronic rhinosinusitis (CRS) is largely unknown, but it is thought that different inflammatory profiles are responsible for the different CRS subtypes. 25-hydroxyvitamin-D (25-VD3) has been shown to alter inflammatory mediators in other disease processes and 25VD3 deficiency is associated with CRS with nasal polyps (CRSwNP), but it is unknown if 25VD3 levels impacts local inflammation in CRS. This study investigated the correlation between plasma 25-VD3 and sinonasal mucus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…It appears that sinonasal epithelial cells express 1-α-hydroxylase and can produce 1. 22 These studies are in accordance with our findings that the incidence of CRSwNP increases with the age, mean age of onset being 42 years.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It appears that sinonasal epithelial cells express 1-α-hydroxylase and can produce 1. 22 These studies are in accordance with our findings that the incidence of CRSwNP increases with the age, mean age of onset being 42 years.…”
Section: Resultssupporting
confidence: 93%
“…A study done by Sansoni et al (2015), there were 26 (45.6%) males and 31 (54.5%) females. 22 A study done by Sedaghat et al (2015), there were 59.2% females and 40.2% males. 23 In our area most of the females are housewives and they mostly remains indoor which might be the reason for low vitamin D levels as well as increased incidence of CRSwNP.…”
Section: Resultsmentioning
confidence: 93%
“…The full texts of the remaining 25 articles were reviewed, with 18 publications excluded because they did not meet the inclusion criteria. Seven articles were included in the final review 2228 (four prospective and three retrospective studies), with a total of 513 patients. However, five of the studies were from the same group, 2226 and, therefore, it is highly likely that the same patients were included in more than one study.…”
Section: Resultsmentioning
confidence: 99%
“…This final group of studies included one study of patients entirely with CRSwNP, 23 two mixed cohort studies of CRSsNP and CRSwNP, 25,28 and four studies that compared CRS subtypes and controls. 22,24,26,27…”
Section: Resultsmentioning
confidence: 99%
“…Several studies suggest that vitamin D3 acts as a steroid hormone that has anti-inflammatory effects 7-9 and plays an important role in regulating dendritic cells (DC) 10 . The mechanism of immune system modification by vitamin D3 is similar to other corticosteroids 710-12 . Various studies have shown that vitamin D3 is able to stop the production of cytokines and inhibit differentiation of immune cells.…”
Section: Introductionmentioning
confidence: 99%